Corporate Social Responsibility (CSR): Strategy for University Sustainable Competitive Advantage - Abubakar, Ahmed; Yauta, Sani Ahmed; Khalifa, Mohammed Mahmud (Business Management and Strategy, 2022)
Corporate Social Responsibility (CSR) is generally presumed to be associated with companies in the full sense of the word, overlooking the important role of other institutions and organizations in achieving the objectives of the concept of CSR. This study's goal is to scientifically evaluate the link between corporate social responsibility and a university's sustainable competitive advantage. A conceptual model was created based on strategic corporate social innovation literature. The research was quantitative, and the variables were measured using the literature guide to build the research questionnaire. The analysis used structural equation modelling and the result revealed that Corporate Social Responsibility in relation to Customers or/and Students (CSRCS), Employees (CSRE), Government (CSRG) and Social stakeholders (CSRS) has a major impact on a university's sustained competitive advantage. Management and employees at universities can learn how to apply differentiation techniques to address community issues related to healthcare, economic, sociocultural, and environmental. For quality research and community outreach that better fulfill social needs, innovative, quality-based approaches must be developed. The study extends the existing literature by empirically validating the relationship between CSR and a university's sustainable comparative advantage.